2019
DOI: 10.1016/j.carbon.2018.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Pattern evolution characterizes the mechanism and efficiency of CVD graphene growth

Abstract: Growing large-area, high-quality monolayers is the holy grail of graphene synthesis.In this work, the efficiency of graphene growth and the quality of their continuous films are explored through the time evolution of individual domains and their surface coverage on the substrate. Our phase-field modeling results and experimental characterization clearly demonstrate the critical roles of the deposition flux, edgereaction kinetics and the surface diffusion of active carbon sources in modulating the pattern evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 32 publications
5
25
0
Order By: Relevance
“…We employ a phase-field simulation , to understand the morphological evolution of MoS 2 crystals. The phase-field model accounts for the adatom diffusion and the evolution of the order parameter ψ (1 for MoS 2 and −1 for bare substrate).…”
Section: Phase-field Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We employ a phase-field simulation , to understand the morphological evolution of MoS 2 crystals. The phase-field model accounts for the adatom diffusion and the evolution of the order parameter ψ (1 for MoS 2 and −1 for bare substrate).…”
Section: Phase-field Modelmentioning
confidence: 99%
“…In 2D material CVD growth, adatom diffusion on the substrate, edge kinetics, and precursor flux are three major physical parameters that govern growth dynamics. Phase-field models provide a means to understand the effects of these parameters on the morphology evolution of 2D materials. Meca et al . investigated the effect of substrate anisotropy and precursor flux on graphene morphology.…”
mentioning
confidence: 99%
“…In experiments, the hydrogen flow rate directly controls the generation rate of free carbon atoms ( F ) from deposition, adsorption and decomposition processes on the exposed copper surface ( φ < 0), as well as the etching rate ( r e ) from the as-grown graphene domain. It has been reported that the etching effect increases with hydrogen flow rate, while growth is promoted as hydrogen increases at low flow rates but decreases at high hydrogen flow rates [ 34 , 49 ]. Specifically, we assume an initial gap distance of 16 Å and 2 L = 20 Å and choose the parameters F , r e accordingly in our model (see details in Supplementary Note 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that graphene exhibits a variety of shapes, including triangle [14], rectangle [15][16][17][18], hexagon [19][20], U shape [21], circular [22], and dendrites [11,[23][24]. Although graphene with different morphologies could be customized by adjusting the ratio of the hydrogen and argon carrier gas mixture [23,25], the influence of the ratio of methane to hydrogen (CH 4 /H 2 ) on the formation of graphene with different morphologies was not reported systematically.…”
Section: Introductionmentioning
confidence: 99%
“…Although graphene with different morphologies could be customized by adjusting the ratio of the hydrogen and argon carrier gas mixture [23,25], the influence of the ratio of methane to hydrogen (CH 4 /H 2 ) on the formation of graphene with different morphologies was not reported systematically. The growth of fractal graphene along a preexisting scratch has been reported [24,26], while the phenomena of stitching together and stacking fractal graphene with different angles are still unrevealed. Here, two main morphologies of graphene (i.e., dendrites and hexagon) were obtained by adjusting the volume ratio of CH 4 /H 2 from 1:50 to 1:100.…”
Section: Introductionmentioning
confidence: 99%